Global Monitoring Report on Financial Protection in Health 2021 - World Health Organization; World Bank (World Health Organization and World Bank, 2021)
Financial protection is an intrinsic part of universal health coverage (UHC) and, together with service coverage, is one of the health systems’ goals. Financial protection is achieved when: there are no financial barrier to access; and direct payments required to obtain health services (outof-pocket health spending) are not a source of financial hardship. A full account of financial hardship requires monitoring of impoverishing health expenditures, including any amount spent on health out-of-pocket by the poor, in addition to large out-of-pocket health spending. Out-of-pocket (OOP) health spending is an inefficient and inequitable way of financing health and should be reduced as much as possible in favour of pre-payment mechanisms. When it contributes to health financing, it should not be borne disproportionately by the poor and not at all by the poorest. Since 2015, the World Health Organization (WHO) and the World Bank have been reporting progress on reducing financial hardship at the global level using two main indicators: i) the incidence of catastrophic health spending, defined as the population with large OOP spending in relation to household consumption or income (Sustainable Development Goal (SDG) indicator 3.8.2 with ‘large’ defined using two thresholds 10% and 25%); and ii) recognizing that even lower thresholds of OOP health spending in consumption or income can lead to financial hardship, the proportion of the population impoverished by OOP health spending. This report goes one step further, to include a focus on the poor spending any amount on health OOP. Those payments matter: they represent a major challenge to “End poverty in all its forms everywhere” (SDG 1) arising from OOP health spending by the poorest. Tracking all OOP health spending is critical to monitoring financial hardship across the whole population, in line with the pledge to leave no one behind that is at the heart of the SDGs.